Enhanced compatibility and mechanical properties of carboxylated acrylonitrile butadiene rubber/styrene butadiene rubber by using graphene oxide as reinforcing filler. (15th February 2017) - Zhang, Xumin; Xue, Xiaodong; Yin, Qing; Jia, Hongbing; Wang, Jingying; Ji, Qingmin; Xu, Zhaodong
Abstract: This work reports a novel compatibilizer and reinforcing filler, graphene oxide (GO), which significantly improved the thermal and mechanical properties of immiscible carboxylated acrylonitrile butadiene rubber (XNBR) and styrene butadiene rubber (SBR) blends. The observed glass transition temperature shift of XNBR/SBR blends demonstrated the improved compatibility of XNBR and SBR. The analysis by Fourier transform infrared spectra and Raman spectroscopy indicated that GO could form both hydrogen bonding with XNBR and π - π conjugation with SBR, which favored the compatibility of XNBR and SBR components in the blends. This unique amphiphilic character of GO enabled it interact with both polar and non-polar components and significantly improve the mechanical properties of the system. With incorporation of only 0.3 phr (parts per hundred rubber) GO, the tensile strength and tear strength of XNBR/SBR blend increased by 71% and 94%, respectively. The temperature of the maximal rate of degradation process improved by 10 °C, and a higher resistance to swelling in toluene was obtained as well. This work suggests the GO has the potential to be a suitable reinforcing filler and compatibilizer in the immiscible XNBR/SBR blends.